MSME Development Strategy in Facing Digital Competition in Padang City - Kusuma wijaya; Devi Maya Sofa; Achmad Wicaksono; Ali Hardana; Haldi Jofanda (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
MSMEs play a vital role in the local economy but are often caught in a "digital transition trap." This study analyzes strategies to strengthen MSME competitiveness by examining the gap between digital awareness and practical optimization. To ensure empirical depth, a mixed-methods approach was employed, combining a survey of 50 MSMEs in Padang with in-depth interviews. Results show that while 63% use social media, only 28% utilize paid ads due to risk-aversion and limited algorithmic knowledge. Furthermore, qualitative findings highlight a "pseudo-digitalization" phenomenon where MSMEs remain platform-dependent without owning their brand data. Although 58% use digital payments, 46% still lack financial literacy. The study theoretically contributes to the concept of "Digital Independence" and provides a practical roadmap for sustainable mentoring over one-time training. This transition is crucial for achieving long-term competitive autonomy and business resilience in Padang City.